Acoustophoretic focusing effects on particle synthesis and clogging in microreactors. Issue 2 (18th December 2018) - Dong, Zhengya; Fernandez Rivas, David; Kuhn, Simon
Abstract : An acoustophoretic microreactor to manage particles in flow and to control the material synthesis process. Abstract : The handling of solids in microreactors represents a challenging task. In this paper, we present an acoustophoretic microreactor developed to manage particles in flow and to control the material synthesis process. The reactor was designed as a layered resonator with an actuation frequency of 1.21 MHz, in which a standing acoustic wave is generated in both the depth and width direction of the microchannel. The acoustophoretic force exerted by the standing wave on the particles focuses them to the channel center. A parametric study of the effect of flow rate, particle size and ultrasound conditions on the focusing efficiency was performed. Furthermore, the reactive precipitation of calcium carbonate and barium sulfate was chosen as a model system for material synthesis. The acoustophoretic focusing effect avoids solid deposition on the channel walls and thereby minimizes reactor fouling and thus prevents clogging. Both the average particle size and the span of the particle size distribution of the synthesized particles are reduced by applying high-frequency ultrasound. The developed reactor has the potential to control a wide range of material synthesis processes.